CHINA-SOUTH AFRICA HIGH-LEVEL PEOPLE TO PEOPLE EXCHANGE MECHANISM SEBAGAI SOFT DIPLOMACY TIONGKOK DI REPUBLIK AFRIKA SELATAN - Naufal Rizki Putra Yasa; Reni Windiani; Fendy Eko Wahyudi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
ABSTRACT This research aims to describe how China’s soft diplomacy policy forms in spreading culture in the Republic of South Africa through the China-South Africa High-Level People to People Exchange Mechanism to increase the arrival of African tourists to China and to find out the dynamics of China’s tourism cooperation with the Republic of South Africa. This research based on the promotion of Chinese culture in the Republic of South Africa under cultural cooperation through the China-South Africa High-Level People to People Exchange Mechanism policy and its relation with tourism cooperation between China and the Republic of South Africa. Using the Soft Diplomacy Concept, this research analyses the cultural promotion activities carried out by China in the Republic of South Africa under the China-South Africa High-Level People to People Exchange Mechanism in 2017. The result shows that there was an increase in African tourist arrival to China in 2018, a year after the promotion of Chinese culture under the China-South Africa High-Level People to People Exchange Mechanism, this increase also exceeded the average percentage of African tourist arrivals to China in a period of 10 years (2008-2018). In 2019, two years after the soft diplomacy measure was implemented, there was a very drastic increase in the arrival of African tourists in China. Based on that result, this research suggested for further research to continue to examine China’s use of soft diplomacy, because soft power itself has been refered to in the 17th National Congress of the Chinese Communist Party. Keywords: China, Republic of South Africa, China-South Africa High-Level People to People Exchange Mechanism, Tourism, Soft diplomacy